Estimation of Interregional Trade for Finnish Regions in 1996 and 2002 - Freight Flow and Gravity Approaches - Tuomas Louhela (European Regional Science Association (ERSA), 2006)
When interregional trade flows were estimated in Finland for the year 1996 the survey was sent to almost 10,000 establishments in manufacturing, construction and service industries. In the regional input-output project for the year 2002 time consuming survey was replaced by integrating commodity and freight statistics. This freight flow method was used for the years 1996 and 2002 to calculate trade flows for Finnish regions. The estimation results were then compared to the survey's trade flow information. Estimations were also made for these years by the gravity approach to increase the knowledge how this traditional method works on the regional level. According to the research results the survey approach and the freight flow and gravity models estimated the order of the flows in the same way for 1996, but the freight flow model underestimated trade between smaller regions. When single flows were compared, the results of the gravity approach differed greatly from the flows gained by the other two methods. The freight flow approach, however, had also a limitation: the data. As commodity statistics do not cover all sale, service and primary products, flows of those goods are still unsolved. The next step in the input-output project is to correct this limitation and sharpen up the picture of the regions' production structure and sales volume.
Keywords: 330